Extrinsic attributes that drive consumer purchase of block mozzarella - K. Homwongpanich; M.E. Watson; D. Rovai; H. Eshpari; M.A. Drake (Journal of Dairy Science)
ABSTRACT: Consumer demand for cheese continues to increase with mozzarella being one of the primary cheeses in the United States. The objective of this study was to understand the effect of extrinsic attributes on consumer desires for block mozzarella cheese. An online survey was conducted with mozzarella consumers (n = 437). Adaptive choice-based conjoint and Kano modeling were used to determine the importance of attributes applicable to block mozzarella. Maximum difference scaling was applied to further quantify the appeal of 23 label claims or messages. Subsequently, 2.5-h immersive qualitative focus groups were conducted (n = 28 consumers) that included mozzarella usage occasion discussion, naming identification, block mozzarella sorting, label discussion, and group tasting. Survey data were evaluated by univariate and multivariate statistics. The ideal block mozzarella for consumers was made from whole milk, had a firm texture or shreds well, block or bar shape, with a resealable package and farmer-owned labeling. Milkfat amount and label claims were the most important attributes (P < 0.05) across all consumers from conjoint analysis. Consumers found “produced without added hormones,” “made with milk from our pasture-raised cows,” and “made locally” to be the most appealing label claims. Consumer segmentation identified a natural cluster (n = 243) which assigned high utility to claims such as “all natural” and “organic” while the flavor cluster (n = 194) assigned high utility to “established business for more than 75 years” and “#1 in Italy.” Melt was a must-have attribute for mozzarella consumers while easy to shred and slice was a performance attribute. Block mozzarella is generally a price-driven product, except for special occasions where consumers seek out block mozzarella that they perceive to be of higher quality.